A contribution to the revision of Adorodocia Brenske (Coleoptera: Scarabaeidae: Rutelinae: Adoretini): a new peculiar species from Ankaratra, Madagascar - Frolov, Andrey V.; Montreuil, Olivier (Zootaxa, 2018)
The recently revised genus Adorodocia Brenske, 1893 (Coleoptera: Scarabaeidae: Rutelinae: Adoretini), comprises 17 species, one of them represented by two subspecies (Montreuil & Frolov 2014). This genus forms, together with Paradorodocia Machatschke, 1957 (four species: Montreuil 2010), and Metadorodocia Machatschke, 1957 (two species: Akhmetova & Montreuil 2010), the subtribe Adorodociina Ohaus, 1912, endemic to Madagascar (Ohaus 1912). Representatives of this subtribe are characterized by a strong prominent prosternal apophyse. In addition, all the species of this subtribe have a rather large body and bear a few strong long hairs on the apical hump of the elytra and more or less strong scale-like setae distributed over the elytra.